2018
DOI: 10.1080/19942060.2018.1542345
|View full text |Cite
|
Sign up to set email alerts
|

Developing an ANFIS-based swarm concept model for estimating the relative viscosity of nanofluids

Abstract: Nanofluid viscosity is an important physical property in convective heat transfer phenomena. However, the current theoretical models for nanofluid viscosity prediction are only applicable across a limited range. In this study, 1277 experimental data points of distinct nanofluid relative viscosity (NF-RV) were gathered from a plenary literature review. In order to create a general model, adaptive network-based fuzzy inference system (ANFIS) code was expanded based on the independent variables of temperature, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 67 publications
1
54
0
Order By: Relevance
“…Nanofluids are defined as a fluid that contains nanometer‐sized particles (nanofibers, nanorods, nanotubes, nanoparticles, nanowires, and nanosheets) . The viscosity, thermal conductivity, and specific heat and density are the important parameters influencing the transfer of heat in the devices . Because of the importance of increasing and decreasing the temperature in industrial applications, temperature conductivity has found many applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanofluids are defined as a fluid that contains nanometer‐sized particles (nanofibers, nanorods, nanotubes, nanoparticles, nanowires, and nanosheets) . The viscosity, thermal conductivity, and specific heat and density are the important parameters influencing the transfer of heat in the devices . Because of the importance of increasing and decreasing the temperature in industrial applications, temperature conductivity has found many applications.…”
Section: Introductionmentioning
confidence: 99%
“…30 The viscosity, thermal conductivity, and specific heat and density are the important parameters influencing the transfer of heat in the devices. 31,32 Because of the importance of increasing and decreasing the temperature in industrial applications, temperature conductivity has found many applications. In high-speed performance, it results in an increase in the amount of temperature that results in the operation at high power and high energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…In order to do the experiment and the evaluation, the proposed model was applied in a tropical environment and several metrics such as the coefficient of determination (r), Nash-Sutcliffe efficiency (Ens), Willmott's Index (WI), root-mean-square error (RMSE) and mean absolute error (MAE) were computed [29]. Recently in 2019, Baghban et al [30] proposed a new approach to develop a general model for predicting nanofluid relative viscosity (NF-RV) [30]. To achieve the goal, expansion of an adaptive network-based fuzzy inference system (ANFIS) was performed [30].…”
Section: Introductionmentioning
confidence: 99%
“…Recently in 2019, Baghban et al [30] proposed a new approach to develop a general model for predicting nanofluid relative viscosity (NF-RV) [30]. To achieve the goal, expansion of an adaptive network-based fuzzy inference system (ANFIS) was performed [30]. The proposed model can be used as a tool for helping chemists and engineers who are involved with nanofluids in their works [30].…”
Section: Introductionmentioning
confidence: 99%
“…A few relationships were derived by Alimoradi et al [40], to estimate the Nusselt number of these sort of heat exchanger. According to the literature review, by using size and volume fraction of solid phase in addition to temperature accurate predictive models are achievable for a single nanofluid [41][42][43][44][45]. In this article, the data were gathered from different studies [46][47][48][49][50] to achieve a comprehensive model applicable in various operating conditions.…”
Section: Introductionmentioning
confidence: 99%